Easy Way To Determine The Feasibility Of Coarse Aggregate On All Pavement Layers Using The Los Angeles Tatonas TA-700 Machine - Mahardi Kamalika Khusna Ali; Agata Iwan Candra; Elsa Rizqi Purwanti; Rikha Wirda Izzati; Kavindo Yugiswara Hutama; Mohammad Roziq; Herlangga Duta Pramudya (U Karst, 2021)
The use of coarse aggregate with poor quality can cause bumpy roads, cracked roads, potholes, and others. Coarse aggregate wear is an indicator of the aggregate resistance index against friction with other objects. Any aggregate to be used in a pavement mix must meet the wear requirements. Low wear causes the aggregate to be easily crushed when exposed to friction and has an impact on a low level of stability. The purpose of this research is to determine the feasibility of coarse aggregate in Kedak Village, Kediri. One of the feasibility of coarse aggregate is reviewed based on wear with abrasion testing. This research was conducted by using an abrasion test using the Los Angeles TA-700 machine and SNI 2417:2008 as a reference. The specimens were taken at random and met the criteria for passing the number 3/4 sieve and stuck on the 2500 gram sieve number 1/2 and the aggregate that passed the 1/2 sieve was stuck on the 3/8 sieve as much as 2500 grams. The results obtained stated that the average wear of the abrasion test was 26.6%. Based on these results, the aggregate can be said to be feasible because it does not exceed 40% in accordance with the provisions of the 2018 Binamarga General Specifications. So that coarse aggregate from Kedak Village, Kediri can be used for all mixtures of road pavement layers.